Empowering Women’s Mental Health In The Metaverse: The Mediating Roles Of Cyberchondria And Technophobia In Digital Healthcare Adoption - Rajan, Padmaja; Dhandapani, Siva kumar (Journal of Neonatal Surgery, 2025)
The metaverse represents an evolving frontier in digital health, offering new pathways for delivering care through immersive technologies. This research investigates the effects of metaverse-enabled digital health platforms on women’s mental well-being, focusing on how cyberchondria and technophobia alter this impact. A structured quantitative survey was conducted with female users familiar with healthcare services in the metaverse. Data analyzed through SPSS and AMOS demonstrated a positive relationship between digital healthcare usage and mental health enhancement. However, elevated levels of cyberchondria and technophobia moderated this relationship, reducing the potential benefits. These findings suggest that while metaverse healthcare expands mental health support, psychological barriers may hinder its effectiveness